Legal protection of the welfare of farmed animals during slaughter - Jachnik, Eliza (Przegląd Prawa Rolnego, 2021)
The main objective of this article is to determine the level of protection of the welfare of farmed animals at the time of slaughter. The analysis of international, European as well as national laws indicates a general assumption that the life of animals is a legally protected good. However, there are certain exceptions to this principle, one of the being the slaughter of farmed animals for the purpose of obtaining certain products of animal origin. Generally speaking, protection of farmed animals during slaughter is reduced to the protection of their welfare and assurance of their most humane treatment, if such is at all possible in a situation of killing. The main protective instrument provided for this is the obligation to stun the animals to effectively render them insensible to environmental stimuli. A derogation from this requirement is only envisaged for ritual slaughter. As can be seen, protection of animals at the time of killing, as well as the effective control of such a procedure, poses certain problems.